Autoextraction of Permanent Incisors and Self-Inflicted Orodental Trauma in a Severely Burned Child - Sultan Keles; Gülçin Dogusal; Işıl Sönmez (Hindawi Limited, 2015)
Autoextraction is one type of self-injurious behaviour. In the literature, self-injurious behaviours are observed in syndromes and genetic conditions. However, to the best of our knowledge, SIB and autoextraction in a severely burned patient have not been reported to date. This report describes the self-inflicted trauma and autoextraction in a severely burned child, and the management of the child during and after burn treatment.